Pengaruh Social Media Marketing Terhadap Purchase Intention Dengan Moderasi Perceived Value Pada Produk Dr Ekle’s Skincare - Ros Elvita Gori; Andi Hidayat Muhmin (Masyarakat Ekonomi Syariah Bogor, 2025)
The growth of the local skincare industry in Indonesia has been rapidly increasing, partly driven by the utilization of social media marketing to build closer relationships with consumers. This study aims to analyze the influence of social media marketing, brand image, and brand awareness on purchase intention, as well as to examine the moderating role of perceived value in the case of Dr. Ekle’s Skincare. The population of this research consists of active social media users in Jakarta aged 13–60 years, while the sample comprises 261 respondents obtained through purposive sampling. Data were analyzed using Structural Equation Modeling (SEM) with SmartPLS 4. The results indicate that social media marketing has a significant effect on brand image, brand awareness, and purchase intention, and that brand image significantly affects purchase intention. However, brand awareness does not influence purchase intention, and perceived value was not found to moderate the relationship between social media marketing and purchase intention. This study is limited by its geographic scope and cross-sectional design. Future research is recommended to expand the research area, apply a longitudinal approach, and include additional variables such as brand trust or electronic word of mouth (e-WOM). The findings contribute to highlighting the critical role of social media marketing and brand image in enhancing purchase intention among local skincare consumers.